Analysis of the Effect of Biomass Fuel Feed Rate on the Performance of a 30 Ton h⁻¹ Water-Tube Boiler in a Palm Oil Mill - Muhammad Fajar; Zulham Effendi (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Boilers are among the most important utility units in palm oil mills because they supply steam required for processing fresh fruit bunches. Boiler operating performance is strongly influenced by the biomass fuel feed rate, which directly affects heat generation, steam production, and thermal efficiency. This study aimed to determine the optimum biomass fuel feed rate for boiler operation and to evaluate its relationship with steam production in a 30 ton h⁻¹ water-tube boiler. A quantitative descriptive approach was employed using operational log sheet data, field observations, and laboratory analyses of biomass fuel characteristics. The observed parameters included fiber and palm kernel shell feed rates, fuel heating value, steam flow rate, steam pressure, steam temperature, feedwater temperature, and boiler thermal efficiency. Boiler efficiency was calculated using the direct method based on the energy balance between heat input and heat output. The results showed that increasing the biomass fuel feed rate increased both total heat input and steam production. Boiler thermal efficiency increased from 61.15% during the initial operating period to a maximum of 71.22% under optimum operating conditions. However, further increases in fuel feed rate did not improve boiler performance, as the efficiency decreased to 70.64%, indicating reduced combustion effectiveness and heat transfer efficiency. These findings demonstrate that proper regulation of biomass fuel feed rate is essential for maintaining stable steam production and achieving optimum thermal efficiency in palm oil mill boiler operations.